2011
DOI: 10.1007/s11252-011-0189-0
|View full text |Cite
|
Sign up to set email alerts
|

The residential landscape: fluxes of elements and the role of household decisions

Abstract: We assessed biogeochemical cycling of elements through residential household landscapes to evaluate the importance of annual to decadal household-level decisions for element fluxes that contribute to urban and regional pollution. We combined a mailed survey, vegetation measurements, and allometric and biogeochemical models to estimate fluxes and accumulation of carbon (C), nitrogen (N), and phosphorus (P) in landscapes of 360 single-family homes in the Minneapolis-Saint Paul, Minnesota metropolitan area. Carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 38 publications
(65 reference statements)
2
32
0
Order By: Relevance
“…The study area comprised seven urban subwatersheds of the Mississippi River in the Capitol Region Watershed (CRW) ( Table 1), building on past studies of household inputs (19,27) and storm drain exports (37). The CRW comprises just over 10,000 ha in Ramsey County, Minnesota, and includes the majority of St. Paul and small portions of neighboring suburbs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study area comprised seven urban subwatersheds of the Mississippi River in the Capitol Region Watershed (CRW) ( Table 1), building on past studies of household inputs (19,27) and storm drain exports (37). The CRW comprises just over 10,000 ha in Ramsey County, Minnesota, and includes the majority of St. Paul and small portions of neighboring suburbs.…”
Section: Methodsmentioning
confidence: 99%
“…Crop nutrient exports from the University of Minnesota St. Paul Campus Agricultural Experiment Station were from published values (64). Nutrients exported in yard waste (leaf litter and grass clippings) were estimated from a previous study in the region (19,27); all yard waste taken to county collection sites is exported from the watersheds. Nutrients exported through spring and fall municipal street sweeping were estimated from tree canopy cover over streets based on a previous study done in a nearby municipality (51).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potentially significant effects of nitrogen addition on unmanaged ecosystems, along with increased human presence near protected areas, have fueled a number of long-term ecological studies on the effects of urbanization on biogeochemical cycles [24,37,39,40]. A recent biogeochemical field study in residential yards found that homeowner practices resulted in large fluxes of N to soils in residential neighborhoods [41], however, a recent chronosequence study of residential yards following conversion from other land uses concluded that residential soils can retain large quantities of C and N over time [42], raising the question of whether N additions in residential land would affect N cycling, and resulting changes in C storage, in protected areas nearby.…”
Section: Introductionmentioning
confidence: 99%